El juego motor para el desarrollo de la inteligencia corporal-kinestésica en niños y niñas de 4 a 5 años paralelo “C”, de la unidad educativa Verbo Divino del cantón Guaranda, provincia Bolívar, año 2023 - Macas Jiménez, Karla Yaili (2024)
Playing is a component of the ludic activities that are present from birth and it is important in the chil development in all the areas. This Project work with the theme: “El juego motor en el desarrollo de la inteligencia corporal-kinestésica en los niños y niñas de 4 a 5 años, paralelo “C” de la Unidad Educativa Verbo Divino, cantón Guaranda, Provincia Bolívar, año 2023 seeks to demonstrate that the motor play is a methodology that can be applied within the teaching-learning process of early childhood, since within this stage they learn better, that is, through experience and interaction with their peers. The approach contained in this Project is mixed, that is, qualitative and quantitative, likewise, for the development of the research, important information has been collected about motor play and how it helps the development of bodily-kinesthetic intelligence in children aged 4 to 5 years, and through the techniques used such as the survey and the observation sheet, it has been possible to determine that there is an incidence between the motor play and the development of bodily-kinesthetic intelligence. For this reason, a guide of activities based on motor games has been designed for the development of the intelligence before mentioned, all of this through a proposal called: “Aventuras con mi cuerpo” This work is successful because each of the objectives such as: establishing, supporting, diagnosing and proposing were achieved, considering that the motor play included in the daily planning is beneficial for the development of the child, since these activities not only promote kinesthetic body intelligence, but also improve concentration, memory and problem solving in each of the students.